Integration of Fiqh al-Muʿamalat and Local Wisdom in the Mawah System of Aceh - Muhammad Ali; Vera Wardani; Ulfatul Karimah; Junaidi (At-Tasharruf "Jurnal Kajian Ekonomi dan Bisnis Syariah", 2025)
This study examines the integration of fiqh al-muʿāmalāt with local wisdom in the mawah system of Aceh and seeks to formulate an ideal model consistent with Sharīʿah principles and contemporary needs. Research was conducted in three regencies Aceh Besar, Pidie, and Pidie Jaya with 30 respondents comprising capital owners, cultivators, traditional leaders, Islamic scholars, village officials, academics, and experts in Islamic economics. Data were collected through participatory observation, in-depth interviews, Focus Group Discussions (FGD), and documentary studies, then analysed thematically and comparatively with reference to fiqh al-muʿāmalāt. Findings indicate that the mawah system remains actively practised in agriculture, plantations, and livestock. It is sustained by values of trust, solidarity, and justice, though agreements are predominantly oral. Profit-sharing patterns vary: 50:50 or 60:40 in agriculture, 70:30 in livestock, and flexible arrangements in plantations. Most respondents regarded mawah as fair (83%), effective in enhancing productivity and equitable distribution (89%), and sustainable in the long term (76%). Comparative analysis shows compatibility with muzāraʿah, musāqāh, and muḍārabah contracts, despite shortcomings in cost transparency and documentation. The study concludes that mawah has strong potential as a sustainable Islamic economic model. Clear contracts, proportional justice, transparency, and adaptive flexibility are key to ensuring its continued relevance and Sharīʿah compliance.